ChemInform Abstract: [3, 3]‐Sigmatropic Rearrangement Step in the Gold‐Catalyzed Cyclization of Allyl‐(ortho‐alkinylphenyl)methyl Ethers. Issue 1 (7th January 2014) - Ackermann, Martin; Bucher, Janina; Rappold, Melissa; Graf, Katharina; Rominger, Frank; Hashmi, A. Stephen K.
Abstract The reaction proceeds via a gold‐catalyzed cyclization step and [3, 3]‐sigmatropic rearrangement with formal inversion of the allylic moiety.